Fertility outcomes following myomectomy in infertile patients at our centre: a retrospective analysis - Goyal, Nidhi; Jayakrishnan, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Fibroids have been known to cause infertility due to multiple factors. However, the role of myomectomy in patients with intramural and subserosal fibroids has been a topic of debate. This study evaluates outcomes following myomectomy in patients seeking treatment for infertility at study centre. Methods: This was hospital based retrospective study which evaluated 92 infertile patients who took treatment for infertility. Results: A total 41.3% patients conceived within one year of myomectomy. Pregnancy rates were better in patients with intramural combined with submucous fibroids, age between 30 and 35 years, size of largest fibroid between 3 and 6 cm and when number of fibroids were between 3 and 6 and conception was maximum after ovulation induction. Conclusions: Pregnancy rates after myomectomy are better in young patients with large fibroids. Active management for infertility needs to be done after myomectomy.